Efficacy and safety of Shugan Jieyu Capsule in the treatment of depressive state after acute coronary syndrome: study protocol for a multicenter randomized controlled trial - Yang, Yankai; Cui, Zhuorui; Yang, Furong; Yu, Yanqiao; Cai, Yajie; Fan, Xiaodi; Yang, Qiaoning; Bai, Ruina (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to evaluate the efficacy and safety of Shugan Jieyu Capsules (SGJY) in patients with depressive state after Acute Coronary Syndrome (ACS).MethodsThis is a multicenter, randomized, double-blind, placebo-controlled clinical trial. A total of 148 patients with depressive state after ACS recruited from five research centers, will be randomly assigned to either the SGJY group or the placebo group at a 1:1 ratio. In addition to standard therapies for ACS, the SGJY group will receive SGJY while the placebo group will receive a matching placebo. All participants will undergo 12 weeks of treatment, followed by 36 weeks of follow-up.ResultsThe primary outcome is the Hamilton Depression Rating Scale (HAMD-17). Secondary outcomes include major adverse cardiovascular and cerebrovascular events (MACCE), Seattle Angina Questionnaire (SAQ) score, depression and anxiety scales, the Short Form-36 (SF-36) health survey, Montreal Cognitive Assessment (MoCA) score, inflammatory cytokine levels, hypothalamic-pituitary-adrenal (HPA) axis activity, and brain-derived neurotrophic factor (BDNF) levels. Safety will be evaluated based on safety indicators and recorded adverse events. Additionally, metabolomic analysis will be conducted on patient serum samples collected before and after treatment to elucidate the potential metabolic pathways of SGJY ameliorates subthreshold depression after ACS.ConclusionThis trial will evaluate the efficacy and safety of SGJY in managing depressive state after ACS. Additionally, the potential of SGJY to improve long-term prognosis in patients with depressive state after ACS will be assessed.